Attempts to calculate the pseudo-anisotropy of elastic parameters of shales gas formations based on well logging data and their geostatistical analysis - Bała, Maria; Cichy, Adam; Wasilewska-Błaszczyk, Monika (Geology, Geophysics and Environment, 2019)
This paper presents the attempts to calculate the pseudo-anisotropy of elastic parameters for the Silurian and Ordovician shale formations of several wells located in the Baltic basin. For this purpose, well-logging data were used, in particular data recorded with acoustic dipole tools. With the P and S waves velocities available, measured at the dipole setting in two orthogonal directions XX or YY (SFast and SSlow), the elastic ε and γ parameters were calculated. In this paper we evaluate the effect of different factors e.g., porosity, clay and kerogen con-tent on the velocity of anisotropy shale gas formations. A geostatistical analysis of elastic and reservoir properties was carried out in order to determine the character of the variability of Silurian and Ordovician shale formations in all of the studied wells. Semivariograms for each well characterizing the variation of elastic parameters in the vertical direction were calculated.